Impact of Beef Consumption on Saturated Fat Intake in the United States Adult Population: Insights from Modeling the Influences of Bovine Genetics and Nutrition. (29th May 2020) - Casperson, Shanon; Conrad, Zach; Raatz, Susan; Derner, Justin; Roemmich, James; Jahns, Lisa; Picklo, Matthew
Abstract: Objectives: Beef, while a prominent source of high-quality protein in the American diet, is a source of saturated fat. Beef production practices, such as breed selection and nutrition regimens, can influence the nutritional value of meat by reducing the saturated fatty acids (SFA) content. Thus, we sought to determine the extent to which implementing these practices reduces population-level SFA intake to meet the Dietary Guideline for Americans (DGA) recommendation of ≤10% en. Methods: Using reported intakes from the National Health and Nutrition Examination Survey 2001–2016, we determined the contribution of food types to total SFA intake. From these data, nutritional modeling methods were used in which the current fatty acid profile of beef was replaced with that from two different breeds (Angus, the predominant breed in the U.S., and Wagyu, a breed with lower SFA content) and three nutrition regimens (pasture-raised, 15% flaxseed supplementation, and 35% wet distiller's grain (WDG) supplementation) to estimate the contribution of each beef type to total SFA intake in the U.S. adult population. Four levels of replacement were compared - 10%, 25%, 50%, 100%. Results: Daily per capita SFA intake was 10.9% en (10.8–11.0% en, 95% CI). Beef was the third greatest contributor (15%) to per capita SFA intake, behind grain (29%) and dairy (19%) dishes. In general, men consumed more beef fat than women (12.0 g vs. 6.6 g, respectively). SFA intake, as a percentage of total energy intake (% en), from beef was 2.1% en (2.1–2.2% en, 95% CI) in men and 1.6% en (1.6–1.7% en, 95% CI) in women. For each modeled beef, SFA intake decreased with each increase in replacement level. At 100% replacement, SFA intake was reduced by 0.5% (Angus), 2.8% (Wagyu), 1.9% (pasture-raised), 4.1% (15% flaxseed), and 2.6% (35% WDG). Conclusions: Data from this modeling study indicate that decreasing the SFA content of beef through breed selection and nutrition regimens can result in a per capita reduction in SFA intake in the American population. However, modeled SFA consumption remained greater (c. 10.5–10.7% en) than DGA recommended intakes in all age and gender groups. These results demonstrate the importance for Americans to reduce SFA intake from all sources, including beef, to meet daily intake recommendations. Funding Sources: United States Department of Agriculture, Agricultural Research Service.